2019
DOI: 10.1136/bmjstel-2019-000497
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of a video game versus live simulation for disaster training

Abstract: IntroductionDisaster triage training for emergency medical service (EMS) providers is unstandardised. We hypothesised that disaster triage training with the paediatric disaster triage (PDT) video game ‘60 s to Survival’ would be a cost-effective alternative to live simulation-based PDT training.MethodsWe synthesised data for a cost-effectiveness analysis from two previous studies. The video game data were from the intervention arm of a randomised controlled trial that compared triage accuracy in a live simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Disaster triage tools such as START and JumpStart optimize the care of the patients who may survive by allocating more resources to those patients than those who do not have a reasonable chance of recovery 35 . In situations where resources are limited because of an unusually large patient volume, 13 this resource allocation strategy helps prevent overload of the medical system, thereby improving overall population outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Disaster triage tools such as START and JumpStart optimize the care of the patients who may survive by allocating more resources to those patients than those who do not have a reasonable chance of recovery 35 . In situations where resources are limited because of an unusually large patient volume, 13 this resource allocation strategy helps prevent overload of the medical system, thereby improving overall population outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Live simulation is resource intensive as it requires large capital investment to purchase simulation mannequins and equipment, to compensate standardized patient actors, technical simulation personnel, 13 and for clinicians' time while they attend. It also precludes the participation of many HPs who may not be able to physically go to the simulation center or who work during the limited opening hours of the simulation centers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…57,58 The INSPIRE members published a successful simplified strategy to implement SBE cost-effectively by using existing in situ space and redirecting established faculty education allotment. 59,60 A series of studies by Cicero et al [61][62][63] examined the use of SBE to improve pediatric disaster triage. The first set of studies demonstrated enhanced performance/ benefits with an in-person simulation intervention but noted a high cost.…”
Section: Progressmentioning
confidence: 99%
“…The first set of studies demonstrated enhanced performance/ benefits with an in-person simulation intervention but noted a high cost. 61,62 A follow-up project demonstrated similar benefits with reduced cost by using a screen-based simulation platform to deliver the content. 63 Although a clinical simulation center is unlikely to be profitable, it should provide immeasurable value to the organization by incorporating simulation into quality and safety initiatives.…”
Section: Progressmentioning
confidence: 99%